2007
DOI: 10.4028/www.scientific.net/msf.555.291
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Thermodynamics in Crystalline Nanofilms

Abstract: The dispersion law and density of states of phonons in ultrathin films was analyzed in this paper. It turned out that phonons in a thin film require activation energy for exciting. This leads to extremely low specific heat and specific conductivity at low temperatures. Consequences of quoted facts were discussed in detail and their influence on kinetic and thermodynamic properties of thin films is estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…On the other hand, it is well known fact that the more inferior electrical conductor material is (under normal conditions), the better superconductor it becomes [1][2][3][11][12][13]. Due to that, the experimental fact can be concluded and justified, that in spatially very confined structures more qualitative superconductive properties have been achieved.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…On the other hand, it is well known fact that the more inferior electrical conductor material is (under normal conditions), the better superconductor it becomes [1][2][3][11][12][13]. Due to that, the experimental fact can be concluded and justified, that in spatially very confined structures more qualitative superconductive properties have been achieved.…”
Section: Discussionmentioning
confidence: 80%
“…1a). Calculation of thermodynamic characteristics of phonons in film structures was presented in a previous YUCO-MAT conference [4]. Now we have calculated phonon contribution in thermodynamic characteristics of quantum wires and compared these results with previous ones in ultrathin film structures.…”
Section: Introductionmentioning
confidence: 99%
“…But it is also established that poor conductors (under normal conditions) are at the same time the best superconductors, and vice versa [4,[15][16][17][18][21][22][23]. Against this background, it can be concluded that in the spatially very limited structures the best superconducting properties can be expected, or that restriction of the spatial dimensions of the structure plays a major role in improving superconducting properties of material.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of phonon contribution in thermodynamic properties of low-dimensional structures (ultra-thin film and superlattice) was the subject of our previous investigations and has been referred [4,10,11,[15][16][17][18][19][20] in the past period. Here, we will use some of these results in order to compare them with the results obtained in this paper for ultra-narrow wires.…”
Section: Theoretical Analysismentioning
confidence: 99%